Fit to play. Practical tips for faster recovery - Petersen, C. (Medicine and Science in Tennis, 2005)
Author gives some practical tips to help players recover quickly. Important are: 1. Re-Hydrate 2. Re-Fuel 3. Re-Align the body 4. Recovery workouts 5. Regain and Maintain Muscle Length Conclusion: Training and competition fatigue experienced by players is a necessary part of the adaptive training process. The challenge for most coaches and players is to identify which specific capacities are fatigued and then select appropriate recovery strategies to restore the player to a normal functioning state. Training for and playing tennis are both physically and mentally demanding, and recovery sessions must be incorporated into tennis-specific training programs. Coaches and players alike need to be more aware of the importance of restoration and regeneration following heavy workloads and how best to use the equipment, facilities and activities available to facilitate recovery.